2008
DOI: 10.1016/j.alcohol.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol exposure of neonatal rats does not increase biomarkers of oxidative stress in isolated cerebellar granule neurons

Abstract: Oxidative stress is a candidate mechanism for ethanol neuropathology in Fetal Alcohol Spectrum Disorders. Oxidative stress often involves production of reactive oxygen species (ROS), deterioration of the mitochondrial membrane potential (MMP), and cell death. Previous studies have produced conflicting results regarding the role of oxidative stress and the benefit of antioxidants in ethanol neuropathology in the developing brain. This study investigated the hypothesis that ethanol neurotoxicity involves product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Kane et al (2008) evaluate the effect of in vivo ethanol exposure on CGC in vitro . In this model, ethanol was administered to rats in vivo via gavage on PD4 (vulnerable period) and PD14 (resistant period) (92). CGC were isolated 2-24 hours post-treatment, and ROS production and relative mitochondrial membrane potential (MMP) were immediately assessed in viable cells.…”
Section: Introductionmentioning
confidence: 99%
“…Kane et al (2008) evaluate the effect of in vivo ethanol exposure on CGC in vitro . In this model, ethanol was administered to rats in vivo via gavage on PD4 (vulnerable period) and PD14 (resistant period) (92). CGC were isolated 2-24 hours post-treatment, and ROS production and relative mitochondrial membrane potential (MMP) were immediately assessed in viable cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results support the hypothesis that oxidative stress is involved in ethanol-induced neuroapoptosis. However, Kane et al [69] reported that in cerebellar granule cells, isolated from 4-day-old rats exposed to ethanol in vivo, neither ROS production nor neuron death are showed. In addition, 17β-estradiol protects more efficiently against the ethanol-dependent oxidative stress-induced MPT pore opening than PYC an efficient antioxidant [66].…”
Section: Alcohol Induces Apoptotic Cellular Deathmentioning
confidence: 94%
“…Exposure during the first-and second-trimester equivalent has been shown to reduce numbers of not only Purkinje cells but also granule cells (Maier & West, 2001;Servais et al, 2007). Binge-like ethanol exposure during the third-trimester equivalent has been consistently demonstrated to be detrimental to Purkinje and granule cells, causing a significant reduction in their numbers via multiple mechanisms, including oxidative stress, reduction in the activity of neurotrophic factors, alterations in cell migration and axonal outgrowth, and neuroimmune deficits (Chen & Charness, 2008;Goodlett, Horn, & Zhou, 2005;Hamre & West, 1993;Heaton, Mitchell, & Paiva, 1999;Heaton, Mitchell, & Paiva, 2000;Heaton, Paiva, Mayer, & Miller, 2002;Kane, Chang, Roberson, Garg, & Han, 2008;Kane et al, 2011;Kumada et al, 2010;Light, Brown, Newton, Belcher, & Kane, 2002). In addition, exposure during the third-trimester equivalent reduces the frequency of events generated by climbing fiber activation (i.e., complex spikes), an effect that may be a consequence of a reduction in cell numbers in the inferior olive or functional alterations at climbing fiber-to-Purkinje neuron synapses (Backman, West, Mahoney, & Palmer, 1998;Pierce, Hayar, Williams, & Light, 2011).…”
Section: Epidemiology and Clinical Management Of Visceral Obesitymentioning
confidence: 97%